2016
DOI: 10.1002/cpp.2003
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Effects of a Brief Compassion‐Focused Imagery Intervention in Psychotic Patients with Paranoid Ideation: A Randomized Experimental Pilot Study

Abstract: Affiliative imagery work is feasible and appraised positively in psychotic patients. Brief compassion focused imagery increased feelings of happiness and reassurance but did not improve negative self-relating, negative affect or paranoia. Further investigation is warranted to identify which patients benefit most from affiliative imagery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 33 publications
2
62
0
Order By: Relevance
“…Even though self‐compassion is primarily conceptualized as a resilience factor, interventions specifically targeting the counterpart vulnerabilities overidentification and isolation may be useful (Montero‐Marin et al ., ). Previous experimental studies found a significant immediate effect of a brief compassion‐focused imagery intervention on paranoia frequency in a subclinical sample (Lincoln, Hohenhaus, & Hartmann, ), but not in an acute patient sample, in spite of significant effects on self‐compassion and positive emotions (Ascone, Sundag, Schlier, & Lincoln, ). However, increased compassion following compassion‐focused group therapy reduced symptoms of depression and social marginalization in a clinical sample (Braehler et al ., ).…”
Section: Discussionmentioning
confidence: 93%
“…Even though self‐compassion is primarily conceptualized as a resilience factor, interventions specifically targeting the counterpart vulnerabilities overidentification and isolation may be useful (Montero‐Marin et al ., ). Previous experimental studies found a significant immediate effect of a brief compassion‐focused imagery intervention on paranoia frequency in a subclinical sample (Lincoln, Hohenhaus, & Hartmann, ), but not in an acute patient sample, in spite of significant effects on self‐compassion and positive emotions (Ascone, Sundag, Schlier, & Lincoln, ). However, increased compassion following compassion‐focused group therapy reduced symptoms of depression and social marginalization in a clinical sample (Braehler et al ., ).…”
Section: Discussionmentioning
confidence: 93%
“…For patients with high levels of attachment anxiety, an approach that promotes effective self‐regulation (see Wallin, ) may be worthwhile. To target ER, we suggest (1) to identify the prevalent attachment‐specific dysfunctional ER pattern and (2) to select according interventions suited to reduce it, for example via worry interventions (for psychosis; see Foster, Startup, Potts, & Freeman, ), mindfulness (Khoury, Lecomte, Gaudiano, & Paquin, ), or compassion‐focused interventions (Ascone, Sundag, Schlier, & Lincoln, ; Braehler et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Although CFI is not offered as a standalone technique in clinical settings, studying it in isolation enables us to identify whether it alone produces positive experiences or requires groundwork (and if so, what inhibitors the groundwork should target). One-session CFI significantly improved negative affect, self-esteem, and self-reassurance in participants with clinical and subclinical psychosis (Ascone, Sundag, Schlier, & Lincoln, 2017;Lincoln, Hohenhaus, & Hartmann, 2013), suggesting potential promise in clinical populations. However, quantitative group analyses can mask individual variance in treatment response.…”
Section: Facilitators and Inhibitors Of Compassionmentioning
confidence: 91%